Analisis Perencanaan dan Penganggaran Pada Dinas Pendidikan Provinsi Jambi - Meri Darlina; Yannizar Yannizar; Siti Hodijah (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2016)
Abstract This research tried to investigate the analysis of consistency between planning and budgeting in education departement of Jambi Province year 2011 to 2015 which viewed by the planning and budgeting document of education in Jambi Province such as; RPJMD year 2010-2015, Renstra year 2010-2015, RKPD yaer 2011-2015, Renja year 2011-2015, PPAS year 2011-2015, RKA year 2011-2015, and DPA of APBD Education department year 2011-2015. The result of the analysis continuosly was analyzed by using Matrik of Planning and Budgeting Consolidation (MKPP) for investigate level of consistency that occur and analyzed what kind of factors which caused inconsistency and what kind of effort has been done to create consistency between planning and budgeting. The result showed level of planning and budgeting consistency between document of planning and budgeting still low. The highest consistency available in PPAS document and APBD document. The cause of inconsistency is leader policy, human resources limitedness, less coordination between sub-department and SKPD, high frequency of leader commutation and goverment’s role changing. Efforts are being made to achieve consistency between planning and budgeting is the functional improvement of human resource planning, improved coordination between field and education and the establishment of an electronic planning system (E-Planning). Keyword : Consistency, Planning, Budgeting, Education, Region Goverment Abstrak. Penelitian ini bertujuan untuk menganalisis konsistensi antara perencanaan dan penganggaran pada Dinas Pendidikan Provinsi Jambi Tahun 2011-2015 yang dilihat dari dokumen perencanaan dan pengaggaran pendidikan di Provinsi Jambi seperti RPJMD Tahun 2010-2015, Renstra Tahun 2010-2015, RKPD Tahun 2011-2015, Renja 2011-2015, PPAS Tahun 2011-2015, RKA Tahun 2011-2015, dan DPA Dinas Pendidikan APBD Tahun 2011-2015.Hasil analisa tersebut selanjutnya di analisis dengan menggunakan Matrik Konsolidasi Perencanaan dan Penganggaran (MKPP) untuk mengetahui tingkat konsistensi yang terjadi dan menganalisis faktor-faktor apa yang menyebabkan inkonsistensi serta upaya apa yang dilakukan untuk mewujudkan konsistensi antara perencanaan dan penganggaran. Hasil penelitian ini menunjukkan tingkat konsistensi perencanaan dan penganggaran antara dokumen perencanaan dan penganggaran masih rendah. Konsistensi tertinggi ada pada dokumen PPAS dan APBD. Penyebab ketidakkonsistenan adalah kebijakan pimpinan, keterbatasan sumberdaya manusia, kurangnya koordinasi antar bidang dan SKPD, sering terjadinya pergantian pejabat, dan perubahan peraturan pemerintah. Upaya yang dilakukan untuk mewujudkan konsistensi antara perencanaan dan penganggaran adalah peningkatan kualitas sumberdaya manusia fungsional perencana, peningkatan koordinasi antar bidang dan SKPD dan pembentukan sistem perencanaan elektronik (E-Planning). Kata Kunci : Konsistensi, Perencanaan, Penganggaran, Pendidikan, Pemerintah Daerah